Relative contribution of wild foods to individual and household food security in the context of increasing vulnerability due to HIV/AIDS and climate variability - Abu-Basutu, Keitometsi Ngulube (Rhodes University, Faculty of Science, Department of Environmental Science, 2014)
Wild foods are an integral component of the household food basket, yet their quantified contribution to food security relative to other sources in the context of HIV/AIDS, climate change and variability remains underexplored. This study was carried out in Willowvale and Lesseyton which are rural communities in the Eastern Cape province of South Africa. Willowvale is a relatively remote, medium-rainfall coastal community, while Lesseyton is a peri-urban low rainfall inland community. Qualitative and quantitative methods were used to collect data from 78 HIV/AIDS afflicted households with 329 individuals and 87 non-afflicted households with 365 individuals in the two study sites. Households were visited quarterly over 12 months to assess food acquisition methods, dietary intake and quality, and levels of food security, and to determine strategies employed by households to cope with droughts. The wild foods investigated were wild meat, wild birds, wild fish, wild mushrooms, wild leafy vegetables and wild fruits. Diets were moderately well-balanced and limited in variety, with cereal items contributing 52 % to total calorie intake. Mid-upper arm circumference measurements showed that all respondents were adequately nourished. The bulk of the food consumed by households was purchased, with supplementation from own production, wild vegetables and wild fruits. In Willowvale, wild vegetables comprised 46 % of overall vegetable consumption for afflicted households and 32 % for non-afflicted households, while own fruit production comprised 100 % of fruit consumption. In Lesseyton, wild vegetables comprised only 6 % and 4 % of vegetable consumption for afflicted and non-afflicted households, while wild fruit comprised 63 % and 41 % for afflicted and non-afflicted households. More than 80 % of respondents from both afflicted and non-afflicted households had sufficient daily kilocalories, although the majority of afflicted households felt they were food insecure and sometimes collected wild foods as one of their multiple coping strategies. Hunting and gathering of wild foods was associated with site, household affliction status, gender, age and season. More than 80 % of respondents ate wild vegetables and said they were more drought tolerant than conventional vegetables, making them the most consumed wild food and approximately 16 % of respondents ate wild birds, making them the least consumed wild food. Approximately 14 % of respondents from afflicted households in Willowvale sold wild fish, whilst 34 % of respondents from afflicted households and 7 % from non-afflicted households sold wild fruits in Lesseyton. Strategies adopted by households to cope with droughts were different between the two study sites, and households in Willowvale used a wider range of strategies. Given the devastating effects of HIV/AIDS coupled with the drawbacks of climate change and variability on food security, wild foods represent a free and easy way for vulnerable households to obtain food.
Keywords: Wild foods -- South Africa -- Eastern Cape; Food security -- South Africa; Food supply -- South Africa; AIDS (Disease) -- Social aspects -- South Africa; HIV infections -- Social aspects -- South Africa; Chronically ill -- South Africa -- Economic conditions; Chronically ill -- South Africa -- Social conditions; Food -- Social aspects -- South Africa; Food -- Economic aspects -- South Africa